PROBLEM TO REDUCE LOSS OF DRINKING VODYV NETWORK WATER SUPPLY - and (Municipal economy of cities. Series: «Economy science», 2013)
The sources of losses are considered from the plumbing network of city, reasons defiant losses, the methods of finding losses are considered devices for finding out a place and organization of controller’s service in these terms